Adopción de las normas internacionales de información financiera (NIIF), para la Cooperativa de Ahorro y Crédito Sinchi Runa ltda. de la provincia de Cotopaxi, cantón Saquisilí, al año terminado 2012 - Casa Lema, Rosa Elvira (2015)
The present research work was developed in the Cooperative Savings and Credit "SINCHI RUNA LTDA.", Located in Saquisilí Canton, Cotopaxi Province, by means of this, it was determined that the entity did not have an appropriate accounting management that allaus it to improve success the uptake, of new partners as well as of new policies as a strategy to obtain higher profitability, associated to a determined period. To obtain a clear and accurate information techniques were employed as interviews, surveys and observation, executed directly to the Executive Staff, Administrative and to the partners with the gathered information might be perform all the analyzes relating to accounting manage and financial, of which help in determining the feasibility….